Implementasi Penerbitan Dokumen E-KTP Huruf Braille Sebagai Inovasi Pelayanan Publik Bagi Penyandang Disabilitas Netra - Sucahyo, Imam; Rahmadi, Andhi Nur; Hadi, Fiqri Akbaruddin (Public Policy, 2023)
Providing social justice for all Indonesian people is our collective duty. In realizing it, the forms of justice obtained are various, such as getting equal rights. One form of obtaining equal rights is public services for persons with disabilities. In accordance with the regulations contained in Law No. 8 of 2016, it says that persons with disabilities have the right to receive the same public services. Like one of the special services. In supporting public services for special services, namely in the form of innovation. One of the innovations made by the Department of Population and Civil Registration of Malang City is the issuance of Braille E-KTP documents for persons with disabilities. However, the problem is that there are still many who have not received Braille documents. In this study using descriptive qualitative research methods with the theory of policy implementation from George Edwards III which has 4 variables namely, Communication, Resources, Disposition and Bureaucratic Structure. The results of this study, it was found that the four variables previously stated had gone well and were in accordance with what happened in the field. It just needs to be improved in order to further increase its utilization